Legal Protection for Creators in Copyright Infringement through E-Commerce - Kornelis Agung Pringgohadi; Cindy Ayu Alvianti; Moch. Firman Adi Prasetyo; Levi Fernanda Taalungan (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
The background of this research is that numerous incidents of copyright infringement, such as piracy, theft, and plagiarism, occur on e-commerce platforms; this is obviously detrimental to the producer of an intellectual work. This research aims to find a form of legal protection for creators for copyright infringement of their intellectual works on e-commerce platforms. The research method used is the normative legal research method with a statutory and conceptual approach, where this method is used to analyze and study several regulations governing copyright infringement and violations in the field of information technology, as well as several legal books and journals that discuss protection law for creators, and e-commerce platforms. The result of this research is the discovery of 2 (two) forms of legal protection for creators of copyright infringement through e-commerce, based on Philips M. Hadjon theory of legal protection, namely: First, preventive legal protection implemented in the form of Copyright Registration as a form of certainty law for creators to obtain concrete evidence regarding ownership of their copyrights; and Second, repressive legal protection implemented in the form of Law no. 28 of 2014 concerning Copyright and Law no. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, which regulates ways to deal with copyright infringements by imposing sanctions in the form of Administrative Sanctions, Civil Sanctions, and Criminal Sanctions.